FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN LAMA WAKTU ADAPTASI PSIKOLOGIS FASE LETTING GO PADA IBU POSTPARTUM - Apriyani Darwin; Widia Lestari; Yulia Irvani Dewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
After giving birth, mothers will experience three phases of psychological adaptation, namely the phase of taking in, taking hold and letting go. The letting go phase is a phase that lasts 10 days after giving birth, the mother is able to adjust, take care of herself and take care of the baby independently. This study aims to determine the factors associated with the length of time for the psychological adaptation of the letting go phase in postpartum mothers. This study uses a descriptive correlation method with a cross sectional approach. The questionnaire used is a family support questionnaire with a validity value of r count 0.447-0.979 and a psychological adaptation time questionnaire for the letting go phase with a validated value of r count 0.489-0.923. The sample amounted to 68 respondents with a simple random sampling technique. The analysis used is bivariate analysis using chi square test. The results of statistical tests showed that there was a significant relationship between maternal age (p value 0.000), parity (p value 0.000), type of delivery (p value 0.047), and family support (p value 0.025) with the length of time for psychological adaptation in the letting go phase. in postpartum mothers. While the factors that did not have a significant relationship with the length of time for psychological adaptation of the letting go phase were education (p value 0.220) and work (p value 0.218). The length of time for psychological adaptation of the letting go phase in postpartum mothers is related to maternal age, parity, type of delivery, and family support. The results of this study can be used as educational material for the importance of psychological adaptation of the letting go phase in postpartum mothers.Keywords: Length of Adaption; Postpartum Mothers; Psychological Adaption of Letting Go.